Pertanggungjawaban Pidana terhadap Pelaku dalam Kasus Penganiayaan Berat: Studi Putusan No. 720/Pid.B/2023/PN Lbp - Awaluddin Siregar; Syahrul Bakti Harahap (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2025)
Indonesia is a country that prioritizes law. This has been explained explicitly in the 1945 Constitution. Criminal law in Indonesia is one of the main guidelines in realizing justice. An act is constituted as a crime and formulated in law if the act is assessed by the legislator as an act that endangers a legal interest. By establishing a prohibition against committing an act accompanied by criminal threats/sanctions for anyone who violates it, it means that the law has provided legal protection for these legal interests. In this problem, the researcher focuses on questions and legal objectives regarding legal protection for victims in cases of sibling murder, namely as follows: 1. What are the factors that cause serious abuse based on case number 720/Pid.B/2023/PN Lbp? 2. What is the criminal responsibility for perpetrators in cases of serious abuse based on case number 720/Pid.B/2023/PN Lbp. Research is the most important part of the entire series of activities for writing a scientific work, because to answer the main research problem, the object of the problem described in the problem formulation will be answered. The research location is a place or area where the research will be carried out. The location of this research is the Lubuk Pakam Class I-A District Court located at Jalan Jendral Sudirman No. 58 Lubuk Pakam, Postal Code: 20512, Tel/Fax: (061) 7955861, North Sumatra. Serious maltreatment is an act of violence that is carried out intentionally and results in serious physical injury or even death to another individual. Cases like this not only harm physically, but also emotionally and psychologically for the victims and society in general. An appropriate and effective legal process in handling cases of serious abuse is important to uphold justice, provide protection to victims, and prevent future violence.